2018
DOI: 10.1007/978-3-319-77736-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in Cancer

Abstract: Otto Warburg observed a peculiar phenomenon in 1924, unknowingly laying the foundation for the field of cancer metabolism. While his contemporaries hypothesized that tumor cells derived the energy required for uncontrolled replication from proteolysis and lipolysis, Warburg instead found them to rapidly consume glucose, converting it to lactate [1]. The significance of this finding, later termed the Warburg effect, went unnoticed by the larger scientific community at that time. The field of cancer metabolism l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 36 publications
2
124
0
Order By: Relevance
“…The aberrant glucose metabolism in cancer cells associates with cell proliferation and resistance to radiation and chemotherapy. Tumor cells require higher rates of glucose uptake, and have higher catabolite uptake and use [65,66]. In breast cancer, CCR5 engagement induces Akt phosphorylation, stimulating glucose uptake, glycolysis, the pentose phosphate pathway, fatty acid synthesis, and glutamine metabolism [55].…”
Section: Deregulated Cellular Energetics (Metabolic Reprogramming)mentioning
confidence: 99%
“…The aberrant glucose metabolism in cancer cells associates with cell proliferation and resistance to radiation and chemotherapy. Tumor cells require higher rates of glucose uptake, and have higher catabolite uptake and use [65,66]. In breast cancer, CCR5 engagement induces Akt phosphorylation, stimulating glucose uptake, glycolysis, the pentose phosphate pathway, fatty acid synthesis, and glutamine metabolism [55].…”
Section: Deregulated Cellular Energetics (Metabolic Reprogramming)mentioning
confidence: 99%
“…Recent studies revealed that KD can also be applied to the treatment of some metabolic or endocrine diseases such as obesity, diabetes and hypertension [11,12]. As we know, malignant tumors were also regarded as a metabolic disease due to their altered glucose metabolism, which was tumor cells preferentially utilize glycolysis instead of oxidative phosphorylation to generate energy and other metabolites [13]. Therefore, KD is becoming a promising adjuvant support therapy for cancer treatment in recent years [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most normal tissues get energy through aerobic oxidation of sugar, and glycolysis occurs only in the absence of oxygen (28). The main approach for tumor cells to get energy is glycolysis, and the product of glycolysis is lactic acid (29).…”
Section: Introductionmentioning
confidence: 99%